Human Development Index and Sustainable Development Goals in Banten Province - Toni Anwar Mahmud; Aryanti Dwi Untari; Muhammad Asmawi (Yayasan Keluarga Guru Mandiri, 2025)
Human development is a key indicator for evaluating the success of sustainable development efforts. This research aims to examine the relationship between the Human Development Index (HDI) and the realization of the Sustainable Development Goals (SDGs) in Banten Province, specifically focusing on efforts to reduce poverty and address regional inequality. Utilizing a library research approach, the study draws primarily from official publications issued by the Central Statistics Agency (BPS) of Banten Province and supporting documents and reports relevant to the SDGs. The findings indicate that rising HDI levels in the province generally align with progress in several SDG objectives. Specifically, progress is most evident in SDG 1, which focuses on poverty eradication, and SDG 10, which addresses reducing social and economic disparities. Substantial variations in HDI among districts and cities persist, highlighting regional disparities that challenge the equitable realization of SDG outcomes. The study concludes that HDI can be utilized as a strategic tool for identifying development priorities and assessing the impact of SDG-related programs. This research contributes to the field of development policy by advocating for the integration of HDI indicators with SDG objectives to promote more equitable and inclusive welfare outcomes at both local and global scales.